Alternative algorithms for helicopter control system based on inverse dynamics and its upgrade with the use of a sidestick controller - Efremov, A.V.; Efremov, A.V.; Mbikayi, Z.; Esaulov, S.Y.; Ivchin, V.A.; Miasnikov, M.I. (My University, 2021)
The modern trend of developing highly automated aircraft is characterized by a transition from traditional methods and technical solutions to innovative approaches of creating control systems, inceptors, and displays. This paper deals with the development of helicopter control systems based on inverse dynamics and its integration with a novel type of side stick shaping the pilot output signal such that it is proportional to the control force (Force Sensing Control - FSC). The synergetic effect arising from this integration is also evaluated. The evaluation of the effectiveness of inverse dynamics was carried out through mathematical modeling of the pilot-aircraft system and ground-based simulations.